Advancing the evidence base for child and adolescent psychopharmacology - Samuele Cortese; Carmen Moreno (BMJ Mental Health)
This editorial focuses on the seven studies published in the BMJ Mental Health topic collection Advances in Clinical Psychopharmacology in Children and Young People. Collectively, these articles provide evidence that informs key steps in the psychopharmacological management of children and adolescents with mental health or neurodevelopmental conditions. Papers in this collection contribute to strengthen evidence-based psychopharmacological practice. We look forward to further developments in the field, supported by adequate research funding.